Lactic Acid Bacteria Diversity in the Fermented Wheat Hamoum in West Algeria - Mehel, Benakriche Ben; Djilali, Benabdelmoumene; Ahmed, Mortet (Pakistan Journal of Nutrition, 2016)
The Algerian couscous called Hamoum is prepared from fermented wheat. Historically, the traditional fermented wheat Hamoum (BFH) was considered a food with medicinal properties in the prevention and treatment of many intestinal pathological and physiological complications. This product comes from the storage of wheat for longer than 12 months in an artisanal underground granary called a "Matmora". The fermented wheat product is rich with microorganisms beneficial to health. A microbiological study based on biochemical tests and physiological traits of the endogenous bacterial flora identified 42 lactic acid bacteria strains at different rates (27 lactobacilli with a rate of 65% and 15 lactococci with a rate of 35%). The bacterial strains were Pediococcus pentosuceus 1 (4.8%), Pediococcus acidilactici (7.5%), Streptococcus bovis (4.8%), Streptococcus thermophilus (4.8%), Lactococcus lactis ssp. lactis 1 (7.5%), Lactococcus raffinolactis (4.8%), Lactobacillus pentossus (4.8%), Lactobacillus plantarum (42%), Lactobacillus brevis (7.5%), Lactobacillus ssp. paracasie paracasie 3 (3.5%), Lactobacillus ssp. paracasie 1 (4.5%) and Weissella confusa (2.5%). Most of the lactic acid bacterial strains showed efficient amylolytic and proteolytic activity. Thus, naturally fermented wheat could be used as a dietary adjuvant as a preventive measure against intestinal pathological complications. Additional studies are underway to understand the cellular mechanisms arising from the use of BFH.